Mobile technologies and handheld devices for ubiquitous learning : research and pedagogy - Ng, Wan, 1955- (Hershey, PA : Information Science Reference, 2011)
'The book provides education and IT stakeholders with an overview of what has been implemented with the different types of mobile technologies, their pedagogical differences, evaluations of the learning outcomes, and new ideas for their uses as both pedagogical and research tools'--Provided by publisher.
Includes bibliographical references (p. 299-325) and index.
Keywords: Educational technology; Education -- Effect of technological innovations on; Mobile communication systems; Wireless communication systems; Mobile computing